The use of cake application to improve speaking ability - I Gusti Ayu Dewi Paramita; I Wayan Dana Ardika; Evin Yudhi Setyono; Ni Nyoman Yuliantini; Ni Ketut Suciani (Politeknik Negeri Bali, 2022)
In an era where learning cannot be separated from technology, there are various Android-based applications that are very helpful, interesting and make learning adapt to the learner's time. Learning media is the learning source component that is able to stimulate students to study (Arsyad: 2005). In this paper the learning media is application. One such application is the Cake application. This application is a learning application that deserves to be tested because it has several advantages. One of the advantages of using learning applications is that there is no limited space and time for learners to learn. Learning is no longer limited to lecture rooms or lecture time. learning can be anytime and anywhere. The purpose of this research is to find out whether the Cake application has an effect on students who use it, especially in the speaking field, more specifically the pronunciation. This research is a type of quantitative research with a quasi-experimental approach. The design used is